Penggunaan Metode Ceramah Variasi Yang Disertai Kemampuan Orientasi Terhadap Peningkatan Kualitas Pembelajaran Ekonomi Siswa Kelas X - 8 SMAN 1 Paciran Lamongan - Saiful Arif (STIT Muhammadiyah Paciran Lamongan, 2019)
Abstract: Based on teacher observations identified that students of class X - 8 SMAN 1 Paciran Lamongan in receiving subject matter from teachers in general are still unclear or vague, so the following problems are formulated: Is there any influence of using the variety lectur e method accompanied by the ability of orientation towards learning outcomes Economics of class X - 8 students of SMAN 1 Paciran Lamongan in clarifying understanding about something and to prevent verbalism? The purpose of this class action research aims to familiarize the teacher in presenting economic subject material with variety lecture methods so that students are able to develop special attitudes and skills by thinking critically and creatively in seeing human relationships with the surrounding environm ent. The research took place at SMAN 1 Paciran Lamongan, the activity began with preparations to form 3 groups. Action research planning in each cycle is arranged together based on the observations and reflections of the teacher. Each cycle includes the st ages of observation and action and development planning. The conclusion of the above discussion is (I) Conventional methods in CAR in the field of Economics less influence students to further improve their learning outcomes, (2) Every class action using th e lecture method variations accompanied by orientation can foster students' courage to understand, make examples that are almost similar to those in the reading, as well as the ability to ask questions compared to using conventional methods, (3) The acquis ition of group student learning outcomes taught using the lecture method variations accompanied by better orientation than the group of students who are taught conventionally.